Expression of indoleamine 2,3-dioxygenase in acute myeloid leukemia and the effect of its inhibition on cultured leukemia blast cells - El Kholy, Noura M.; Sallam, Maha M.; Ahmed, Manal B.; Sallam, Reem M.; Asfour, Inas A.; Hammouda, Jehad A.; Habib, Haidy Z.; Abu-Zahra, Fatima (Medical oncology (Northwood, London, England), 2011)
Indoleamine 2,3-dioxygenase (IDO), a catabolizing enzyme of tryptophan, is a novel immunosuppressive agent blocking T-cell activation in neoplastic cells, including acute myeloid leukemia (AML) cells. IDO inhibitors as 1-methyl tryptophan (1MT) can abrogate IDO enzymatic activity and may result in an effective immune response. Mononuclear cells (MNCs) were separated from peripheral blood of 25 AML patients and 25 normal adults. IDO expression was detected by RT-PCR and its enzymatic activity by a colorimetric method. MNCs were cultured and the effects of Adriamycin, 1MT and a mixture of both on blast and lymphocyte cell counts after 24 and 72 h were detected. IDO mRNA and activity were detected in 52% of patients and absent in normal subjects. There was a significant correlation between IDO mRNA expression and its enzymatic activity in AML. IDO activity was correlated positively with patient’s ages and negatively with hemoglobin levels. There was a significant inhibition of blast cells proliferation with Adriamycin and more inhibition when combined with 1MT. The inhibition was more after 72 h more than 24 h of culture. However, using 1MT alone showed no significant inhibitory effect on blast cells, with a significant increase in lymphocyte counts. Our study confirms the role of indoleamine 2,3-dioxygenase in tumor-induced immune tolerance and points to the possible benefit of 1-methyl tryptophan as immunotherapeutic enhancing the anticancer effects of traditional chemotherapeutics.